2017
DOI: 10.18632/oncotarget.16102
|View full text |Cite
|
Sign up to set email alerts
|

The imidazoacridinone C-1311 induces p53-dependent senescence or p53-independent apoptosis and sensitizes cancer cells to radiation

Abstract: C-1311 is a small molecule, which has shown promise in a number of pre-clinical and clinical studies. However, the biological response to C-1311 exposure is complicated and has been reported to involve a number of cell fates. Here, we investigated the molecular signaling which determines the response to C-1311 in both cancer and non-cancer cell lines. For the first time we demonstrate that the tumor suppressor, p53 plays a key role in cell fate determination after C-1311 treatment. In the presence of wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
3
4
0
Order By: Relevance
“…In contrast, AR-negative cells with mutated p53 underwent arrest in the G2/M phase of the cell cycle. These results are in agreement with our previous observations showing that C-1311 has the potential to kill cancer cells with an unfavorable p53 profile [16]. Strategies combining the standard anti-PCa therapy with cell cycle inhibitors targeting the G1 (palbociclib, ribociclib, AZD-5363, ipatasertib) or G2 (adavosertib) phases of the cell cycle are currently tested in several clinical trials in castration-resistant prostate cancer [48].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, AR-negative cells with mutated p53 underwent arrest in the G2/M phase of the cell cycle. These results are in agreement with our previous observations showing that C-1311 has the potential to kill cancer cells with an unfavorable p53 profile [16]. Strategies combining the standard anti-PCa therapy with cell cycle inhibitors targeting the G1 (palbociclib, ribociclib, AZD-5363, ipatasertib) or G2 (adavosertib) phases of the cell cycle are currently tested in several clinical trials in castration-resistant prostate cancer [48].…”
Section: Discussionsupporting
confidence: 92%
“…Next, we assessed the effect of C-1311 on the biological response of the PCa cells. C-1311, as a topoisomerase II inhibitor, has been previously demonstrated to induce DNA damage [ 16 ]. Correspondingly, we found that C-1311 treatment in LNCaP, 22Rv1, and DU-145 cells increased the phosphorylation of the histone H2AX (γH2AX) ( Figure 5 A), a well-known marker of DNA damage [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data demonstrate that, although both VX-970 and VE-821 lead to an accumulation of p62, only VX-970 also impacts LC3. Next, OE21 cells were exposed to VX-970 in hypoxic conditions of <0.1% oxygen, which has been shown to induce autophagy ( Rzymski et al., 2010 ; Skwarska et al., 2017 ). As expected, exposure to hypoxia led to increased LC3-II and a decrease in p62.…”
Section: Resultsmentioning
confidence: 99%
“…Allosteric inhibitors of the CXCR4 receptor block metastasis-associated cell activity stimulated by secretions from irradiated lung epithelial cells and may be effective as cancer therapy when combined with radiation therapy [ 179 ]. Treatment for cancer cells with imidazoacridinone C-1311 (SymadexTM) prior to irradiation causes senescence in the presence of p53 and apoptosis without p53 [ 180 ]. A combination of radiotherapy and drug therapy is also important.…”
Section: P53 and Senescence Induced By Radiation In Cancer Cellsmentioning
confidence: 99%